PENGARUH BELAJAR MANDIRI DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA DI MTS NEGERI 3 KOTA BEKASI - Nafiah, Nafiah; Nurazizah, Indah; Zahra, Alfiah; Ramadhan, Muhammad Rafli; Rahmawati, Rafika (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2023)
This study aims to determine the effect of independent learning variables and student motivation on learning achievement in PAI subjects. The research was conducted at MTsN 3 Bekasi City from November to December 2022. This type of research is quantitative with a correlational descriptive approach, the nature of the data is ex post facto. The sample in this study were 50 students who were taken 20% of the total population of 128 students spread across grades IX A and IX B using a purposive sampling technique. previously validated questionnaires were used to collect data. Data analysis used multiple regression, by carrying out previous classical assumption tests including normality tests, heteroscedasticity tests, autocorrelation tests, and multicollinearity tests. The data analysis carried out yielded the following results: 1) independent learning did not have a significant effect on PAI learning achievement, and 2) learning motivation had a significant effect on PAI learning achievement, 3) independent learning and student motivation together had a significant effect on PAI learning achievement. Based on the results of the F test, the calculated F value is 8.160. At a significance level of 5%, an F table value of 3.231 is obtained. So, F count 8.160 > 3.231 F table Thus, H1 is approved and H0 is rejected. This means that there is a significant influence between independent learning and Learning Motivation on Student Achievement MTsN 3 Bekasi City.